EXTRACTION, PURIFICATION AND CHARACTERIZATION OF LIPASE FROM THE DIGESTIVE DUCT OF COMMON CARP CYPRINUS CARPIO L. - Ali, Hind. K.; Nasser, J. M.; Shaker, K. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to use digestive duct of common carp Cyprinus Carpio L. as economic source for fish lipase extraction . The enzyme was extracted using potassium phosphate buffer (pH 7 , 0.2 M ). The crude extract then precipitated at the saturation range between 40 – 80 % and dialyzed . Further purified carried out through ion exchange chromatography using DEAE-Cellulose column (2.5 × 30 cm) and gel filtration chromatography by Sephadex G-100 column (1.5 x 60 cm). The purified lipase had a molecular weight of 37.150KDa ,and optimum pH and temperature for enzyme activity about 45◦C and 6.5 using olive oil as substrate .The specific activity, number of purification folds and yield of purified Lipase were 146.48U/mg, 9.76 and 40.50% respectively.